Pregnancy in End-stage Renal Disease Patients on Long-term Hemodialysis: Two Case Reports - Selim, Gjulshen; Stojcheva Taneva, Olivera; Tozija, Liljana; Gelev, Saso; Adamova, Gordana; Gerasimovska-Kitanovska, Biljana; Shikole, Aleksandar (Macedonian Society of Nephrology, Dialysis, Transplantation and Artifical Organs, Department of Nephrology, 2010)
Although still uncommon, pregnancy in haemodialysis (HD) patients does occur and frequency has been increased in the past 20 years. But unfortunately, the rates for premature delivery, neonatal death, maternal hypertension, and preeclampsia in the pregnant HD patient are much higher than in the general population. Infants are often born both prematurely and small for gestational age. We report here two cases of pregnancy in women on long-term HD, one successfully and the other unsuccessfully managed, despite the same treatment strategy. Case 1 was a 43-year-old female patient, 10th gravida, after six years of maintenance HD whose pregnancy was successfully managed up to the 33rd week of gestation with a delivery of a healthy boy weighing 2,100 g. Case 2 was a 32-year-old female patient, 2nd gravida, after five years of maintenance HD, whose pregnancy ended in spontaneous abortion with intrauterine death at week 19 of gestation. Maternal hypertension and anemia contributed partly to the unsuccessful outcome. A successful pregnancy in HD patients requires multidisciplinary management, but considering the previous nephrological/ prenatal/gynaecological/obstetric recommendations, many open questions remain when it comes to the best treatment and management of pregnancy in these women.
Keywords: haemodialysis; pregnancy; anaemia; hypertension